Implementasi Aplikasi Pengaduan Masyarakat Berbasis Android Pada Gedung DPRD - Ega Salsa Nugraha; Abdul Robi Padri; Odi Nurdiawan; Ahmad Faqih; Saeful Anwar (JURIKOM (Jurnal Riset Komputer), 2021)
Community complaints are an effort to form the community to contribute to the government's efforts to improve the quality of public services and improve the Cirebon Regency DPRD, the Democratic Party faction in responding to public complaints. Communities who will be able to assist the government in providing information about the quality of services and problems that exist in the environment or their place of residence through government agencies to be followed up immediately. Community complaints in the Cirebon Regency DPRD The Democratic Party faction currently still uses manual recording and still uses WhatsApp messages so that data is not accommodated properly so that complaints that should not be lost and are very helpful both from the community or from the Cirebon Democratic Regency DPRD. So in this final study, we will build an Android mobile-based public complaint application, in the Cirebon Regency DPRD the Democratic Party Fraction and public complaints can be integrated directly to the agencies related to complaints in the community. Public complaints are expected to provide convenience for the government and relevant agencies in providing responses, responses and handling complaints more easily